2015
DOI: 10.4049/jimmunol.1402954
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Regulation of p38α-Mediated Inflammation in Con A–Induced Acute Liver Damage

Abstract: Because p38α plays a critical role in inflammation, it has been an attractive target for the development of anti-inflammation therapeutics. However, p38α inhibitors showed side effects including severe liver toxicity that often prevailed over the benefits in clinical studies, and the mechanism of toxicity is not clear. Here, we demonstrate that p38α regulates the inflammatory responses in the acute liver inflammation in a tissue-specific manner, and liver toxicity by p38α inhibitors may be resulted from the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Clinical trials with certain p38 MAPK inhibitors were discontinued because of liver toxicity [117,125], which is likely to be due to the inhibition of p38α MAPK. This is consistent with studies suggesting that deficiency of p38α in the liver increases the expression of chemokines to recruit more inflammatory cells [126], facilitates N-Nitrosodiethylamine (DEN) -induced hepatocellular carcinoma and increased proliferation [127,128]. In addition, p38α MAPK facilitates bile formation by translocating MRP2 to the PM.…”
Section: Liver Functions Inflammatory Diseases and P38 Mapksupporting
confidence: 90%
“…Clinical trials with certain p38 MAPK inhibitors were discontinued because of liver toxicity [117,125], which is likely to be due to the inhibition of p38α MAPK. This is consistent with studies suggesting that deficiency of p38α in the liver increases the expression of chemokines to recruit more inflammatory cells [126], facilitates N-Nitrosodiethylamine (DEN) -induced hepatocellular carcinoma and increased proliferation [127,128]. In addition, p38α MAPK facilitates bile formation by translocating MRP2 to the PM.…”
Section: Liver Functions Inflammatory Diseases and P38 Mapksupporting
confidence: 90%
“…It is activated by stress, playing an important role also in immune response and in the regulation of cell survival, differentiation, and apoptosis induction. 14 16 p38 inhibitors are being sought for possible therapeutic effect on acute liver disease, 17 prostate 18 and esophageal cancer, 19 autoimmune diseases, and other inflammatory processes, 14 16 for example, pamapimod. 20 For chronic obstructive pulmonary disease and asthma, numerous clinical trials have even been performed with promising results, 21 23 for example, dilmapimod.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we clearly identified that Ccl2/Ccl5 chemotactic signals were crucial in that response as their neutralization sensitized to increase liver injury. Therefore, our findings highlight a new aspect in the pleiotropic role of p38α in hepatocytes during acute liver injury, as until now the beneficial effect of p38α deletion was strictly observed when performed in immune effectors such as liver myeloid cells or T/NKT cells 51,52 . Furthermore, the work of Kang and collaborators provided evidence that p38α ablation in hepatocytes was fueled by a drastic accentuation of liver injury associated with a massive inflammatory cell recruitment 51 .…”
Section: Discussionmentioning
confidence: 61%
“…In the present study, we developed a new inducible and hepatospecific mice model in which p38α isoform was completely deleted in mature hepatocytes. Until now, p38α ablation in the liver was shown as deleterious in different models of liver injury 22,25,51 . In this study, using the CCl 4 model of acute liver injury, we demonstrate for the first time that p38α deletion generated a pro-hepatoprotective response against liver injury.…”
Section: Discussionmentioning
confidence: 99%